2012
DOI: 10.1021/bi300223b
|View full text |Cite
|
Sign up to set email alerts
|

Four-State Folding of a SH3 Domain: Salt-Induced Modulation of the Stabilities of the Intermediates and Native State

Abstract: Unstable intermediates on the folding pathways of proteins can be stabilized sufficiently so that they accumulate to detectable extents by the addition of a suitable cosolute. Here, the effect of sodium sulfate (Na(2)SO(4)) on the folding of the SH3 domain of PI3 kinase was investigated in the presence of guanidine hydrochloride (GdnHCl) using intrinsic tyrosine fluorescence and 1-anilinonaphthalene-8-sulfonate (ANS) binding. The free energy of unfolding in water of the native state (N) increases linearly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 104 publications
2
40
1
Order By: Relevance
“…The mechanism by which a protein achieves its native structure is much more sensitive to environmental tuning than the final native fold itself. Changes in solvent conditions as well as mutations may cause the folding mechanism to switch between a two‐state and a three‐state transition, via destabilization or stabilization of an intermediate. Alternatively, subtle changes in folding conditions may cause a switch from a pathway on which only the N and U states are populated, to a pathway on which folding occurs via the accumulation of intermediates .…”
Section: Tuning the Cooperativity Of Protein Folding And Unfolding Trmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which a protein achieves its native structure is much more sensitive to environmental tuning than the final native fold itself. Changes in solvent conditions as well as mutations may cause the folding mechanism to switch between a two‐state and a three‐state transition, via destabilization or stabilization of an intermediate. Alternatively, subtle changes in folding conditions may cause a switch from a pathway on which only the N and U states are populated, to a pathway on which folding occurs via the accumulation of intermediates .…”
Section: Tuning the Cooperativity Of Protein Folding And Unfolding Trmentioning
confidence: 99%
“…Multi‐step folding is undeniable for many proteins because their folding intermediates are stable enough to accumulate and be easily detectable . In such cases, structural characterization of intermediates provides a wealth of information on folding pathways, and allows different folding pathways to be distinguished from each other .…”
Section: Introductionmentioning
confidence: 99%
“…The DMG is particularly hard to identify in studies of protein folding because it appears to form after the rate-limiting step of folding (8,16). Intermediates that form after the ratelimiting step of folding, however, can be identified from studies of unfolding at high denaturant concentration, and for several proteins (24)(25)(26)(27)(28). In particular, it has been shown for barstar that the same mechanism for unfolding and folding in urea is applicable over the urea concentration range 0 to 7 M (29).…”
Section: Introductionmentioning
confidence: 99%
“…SH3 domains are small globular proteins and are considered to be archetypal of two-state folding proteins . They play important roles in signal transduction, where they provide the interaction surface for multimeric protein complexes. , The SH3 domain of the PI3 kinase was initially characterized as a cooperatively folding protein (two-state folder), , but subsequent equilibrium and kinetic folding studies showed that it (un)­folds via multiple intermediate states. Previous unfolding studies using HX-MS as a probe have shown that the unfolding of the PI3K SH3 domain is a highly heterogeneous process. , The initial structure opening events occur through a continuum of intermediate states. Only at a later stage does the remaining structure unfold in a cooperative manner.…”
mentioning
confidence: 99%